"Unhappy Forever". Method and Issues in Material and Written Records for Me- dieval Archaeology - Galbán Malagón, Carlos (Madrygal. Revista de Estudios Gallegos, 2024)
The divergence between disciplines has led to a growing misunderstanding among researchers based on the nature of the sources, often forgetting the necessity of a non-aprioristic approach to the common record. We present the problems and possibilities of such approach using various examples from the Galician Middle Ages: written documents as objects, relationship between concept and materiality of the architecture of power or the study of seigneurial landscapes. Thus integrating written sources as part of the material record.
Keywords: Written Record; Medieval Archaeology; Fortification; Power Relations; Medieval Galicia